2022
DOI: 10.1017/s0014479722000321
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus cycling byUrochloa decumbensintercropped with coffee

Abstract: Summary Phosphorus (P) is a limiting resource for agricultural production in the tropics. Urochloa spp. is commonly used as a cover crop and has mechanisms to mobilize partially the nonavailable P forms from the soil. The use of Urochloa intercropped with Arabica coffee (Coffea arabica L.) is increasing in Brazil, but P cycling has been overlooked in this system. Here, we proposed two experiments to test the hypothesis that Urochloa decumbens could mobilize and absorb P from deep soil layers and increase ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 40 publications
0
5
1
Order By: Relevance
“…Different AMF species (Acaulospora longula and Acaulospora colombiana) were previously reported by Barbosa et al [8] as associated to U. brizantha in greenhouse, also in Minas Gerais, Brazil Table 1 shows limited available reports on Urochloa species and their associated microbiomes in Brazil. In the present study, the AMF community structure was studied in a grassland in Brazil, The AMF community structure in the U. brizantha experimental plot showed dominance of Glomeraceae, compared to other reports (Table 1) where Acaulospora and Gigaspora were inoculated and, thus, theoretically occurred, such as in the reports by Baptistella et al [6,7]. In the present work, five genera of Glomeromycota, four species and four unidentified morphotypes were detected in the U. brizantha grassland.…”
Section: Resultscontrasting
confidence: 45%
See 3 more Smart Citations
“…Different AMF species (Acaulospora longula and Acaulospora colombiana) were previously reported by Barbosa et al [8] as associated to U. brizantha in greenhouse, also in Minas Gerais, Brazil Table 1 shows limited available reports on Urochloa species and their associated microbiomes in Brazil. In the present study, the AMF community structure was studied in a grassland in Brazil, The AMF community structure in the U. brizantha experimental plot showed dominance of Glomeraceae, compared to other reports (Table 1) where Acaulospora and Gigaspora were inoculated and, thus, theoretically occurred, such as in the reports by Baptistella et al [6,7]. In the present work, five genera of Glomeromycota, four species and four unidentified morphotypes were detected in the U. brizantha grassland.…”
Section: Resultscontrasting
confidence: 45%
“…Furthermore, AMF secret a protein (glomalin), which favors soil aggregation, improving soil quality. In this sense, only one report showed the soil glomalin content in U. brizantha, which, varied from 3.30 to 3.74 mg. g soil −1 when inoculated with G. margarita and A. longula, respectively [6]. The low glomalin content when inoculated with Gigaspora sp.…”
Section: Urochloa Species For Cover Cropsmentioning
confidence: 97%
See 2 more Smart Citations
“…This characteristic is exciting since coffee is also quite colonized and depends on mycorrhizas to acquire nutrients, mainly P, and contributes to the positive water status of coffee plants (Andrade et al, 2009(Andrade et al, , 2010. Moreover, several authors have shown that the roots of Urochloa were active and capable of absorbing nutrients even at a depth of 1m in the interrow of coffee and that they were capable of mobilizing part of the non-readily available P, recycling enough P to satisfy the demand for high coffee yields (Baptistella et al, 2022).…”
Section: Urochloa Intercropping With Coffeementioning
confidence: 99%